Determination of Minerals and Trace Elements in Soils and The Relation with its Concentrations in Sugar Beets - Zehra Kucukbay, F.; Kuyumcu, Ebru; Karaca, Idil; Ozdemir, Durmus (Asian Journal of Chemistry, 2010)
Twelve sugar beets and corresponding soil samples from the plantation near Malatya, Turkey were analyzed for mineral and trace element contents. Thirteen metals (Al, Ca, Cd, Cu, Fe, K, Mg, Mn, Na, Ni, Pb, Se and Zn) were selected and analyzed quantitatively by FAAS/FAES and ETAAS. Principal component analysis and hierarchical cluster analysis were used to explore samples based on the element contents. The principal component analysis analysis of sugar beet samples yielded five principal components which were able to explain about 84 % of the total variance in the data set. The number of principal components that are higher than one was four for the soil samples and were able to explain 83 % of total variance. Hierarchical cluster analysis of sugar beet samples and corresponding soil samples resulted in two main clusters based on the geographic regions of the samples. In terms of the elements being analyzed, the hierarchical cluster analysis method resulted in 3-4 clusters of the elements in both sugar beet and soil samples.